El Derecho Constitucional Económico en el Perú - Arnaldo Castillo Calle, Manuel (Nómadas. Critical Journal of Social and Juridical Science, 2013)
This article is intended to provide some scope on how the Economic System is regulated in our Magna Lex, as we know in our constitutional history of economic regulation in a constitution is not a practice that has always existed, well Conversely, an economic part is included in a new constitution in the twentieth century, adding to those two traditional parties comprising the same, which come to be the dogmatic referred to the rights and duties of the person or citizen, and, an organic part, that is, one dedicated to addressing matters related to the state organization and the different functions performed by each and every one of its component agencies.
Keywords: economic system; partly dogmatic; partly organic constitution; neo-capitalism; democratic socialism; preamble; social market economy; fundamental rights; the State